2006
DOI: 10.1002/ffj.1760
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition of Agastache anethiodora Britton (Lamiaceae) infected by cucumber mosaic virus (CMV)

Abstract: Giant hyssop, Agastache anethiodora Britton, cultivated at the Herb Garden of Casola Valsenio, Italy, has been found for the first time naturally infected by cucumber mosaic virus (CMV). Characteristic symptoms on the leaves were chlorotic or yellow mosaic, ring and line patterns and malformation, followed by yellowing and stunting of the entire plant. CMV was mechanically transmitted to species of the families Chenopodiaceae and Solanaceae and identified by applying PAS-ELISA and RT-PCR techniques. The essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
2
17
0
2
Order By: Relevance
“…Regardless of the plant material, the major compounds were accompanied by several sesquiterpenoids as well as aliphatic (C5, C6, C7, C8, C9) alcohols, aldehydes, esters, and ketones (some of which are known as green leaf volatiles), none of which exceeded 1% of the total VOCs. In essential oil from a related species, A. anethiodora, a drastic decrease in EG and an increase in monoterpene hydrocarbons and isomenthone/menthone was observed upon infection by cucumber mosaic virus (Bruni et al 2007). Several other authors have also reported a great diversity of essential oil composition between samples of different origin (Chae et al 2005;Svoboda et al 1995), but there is no complete explanation of the possible cause of this variation.…”
Section: Resultsmentioning
confidence: 93%
“…Regardless of the plant material, the major compounds were accompanied by several sesquiterpenoids as well as aliphatic (C5, C6, C7, C8, C9) alcohols, aldehydes, esters, and ketones (some of which are known as green leaf volatiles), none of which exceeded 1% of the total VOCs. In essential oil from a related species, A. anethiodora, a drastic decrease in EG and an increase in monoterpene hydrocarbons and isomenthone/menthone was observed upon infection by cucumber mosaic virus (Bruni et al 2007). Several other authors have also reported a great diversity of essential oil composition between samples of different origin (Chae et al 2005;Svoboda et al 1995), but there is no complete explanation of the possible cause of this variation.…”
Section: Resultsmentioning
confidence: 93%
“…26 Viral diseases such as cucumber mosaic virus (CMV), transmitted by aphids, have been detected in several medicinal and aromatic crops. 38 An infection of the giant hyssop (Agastache anethiodora) with CMV was found to induce an 88% reduction in the yield of the essential oil as well as changes in the relative amounts of the oil components. 39 …”
Section: Diseases and Pestsmentioning
confidence: 99%
“…Although the virus has not been identified, it is well known that viral infection can induce varied plant metabolism changes, modifying respiration rates, photosynthesis, and transpiration [17]. However, there are few papers concerning secondary metabolism changes in virus infected plants [12,[21][22][23].…”
mentioning
confidence: 99%